Про одновимірні двохфазні обернені задачі Стефана - Жерновий, Ю.В. (Український математичний журнал, 1993)
New formulations of the inverse nonstationary Stefan problems are considered: (a) forx ∊ [0,1] (the inverse problem IP1); (b) forx ∊ [0, β(t)] with a degenerate initial condition (the inverse problem IPβ). Necessary conditions for the existence and uniqueness of a solution to these problems are formulated.